2004
DOI: 10.1103/physrevlett.93.045001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Electron Holes in an Electron–Oxygen-Ion Plasma

Abstract: The dynamics of electron holes (EHs) in an electron-oxygen-ion plasma is studied by means of Vlasov simulations. It is found that EHs are attracted by ion density maxima but repelled by ion density minima. Standing EHs repel ions owing to the positive EH potential, creating an ion density cavity which ejects the EH, which propagates away from the cavity with a constant speed. On the other hand, propagating EHs can be trapped at ion density maxima. The results of our simulations will help in understanding the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…This should enable the ESWs to remain stable. In contrast, low-speed ESWs with very large potentials would tend to reflect ions, making the ESWs unstable Drake et al, 2003] or accelerating them out of the ion frame [Eliasson and Shukla, 2004]. We conclude that these ESWs are stable because the potentials are too small to significantly scatter or reflections.…”
Section: Warm Bistream Instabilitymentioning
confidence: 82%
See 1 more Smart Citation
“…This should enable the ESWs to remain stable. In contrast, low-speed ESWs with very large potentials would tend to reflect ions, making the ESWs unstable Drake et al, 2003] or accelerating them out of the ion frame [Eliasson and Shukla, 2004]. We conclude that these ESWs are stable because the potentials are too small to significantly scatter or reflections.…”
Section: Warm Bistream Instabilitymentioning
confidence: 82%
“…ESWs are observed with ± polarity and have similar pp . In contrast, low-speed ESWs with very large potentials would tend to reflect ions, making the ESWs unstable Drake et al, 2003] or accelerating them out of the ion frame [Eliasson and Shukla, 2004]. The maximum potential is ≈ 0.14 V, so individual ESWs do not strongly interact with electrons or ions.…”
Section: Warm Bistream Instabilitymentioning
confidence: 99%
“…The total potential energy W pot = (1/2) E 2 dx as a function of time (upper panels) and the minimum of the electrostatic potential (lower panels) for e = −0.7 (left panels) and e = −0.5 (right panels), obtained from the model for a stationary electron hole in the presence of a varying ion density, where the ion density is obtained from the Vlasov simulations (after Ref. [108]). …”
Section: Self-acceleration Of Electron Holesmentioning
confidence: 99%
“…Let us discuss the numerical results for the dynamics of non-relativistic electron holes in an electron-ion plasma [108]. In order to investigate the dynamics of electron holes numerically in a controlled manner, we use Schamel's solution of the stationary Vlasov-Poisson system with immobile ions to construct initial conditions for our simulations.…”
Section: Self-acceleration Of Electron Holesmentioning
confidence: 99%
“…Numerical studies show that the trapped Langmuir waves are Landau damped due to the relatively small Debye-scale of the ion holes (Eliasson and Shukla, 2004a). We have also studied the fully nonlinear interaction between electron holes and oxygen ions by means of a Vlasov simulations (Eliasson and Shukla, 2004b), where it is found that the large-amplitude electron hole potential accelerates the ions locally and that the self-created ion density cavity accelerates the electron hole, which propagates away from the ion cavity with a constant speed close to half the electron thermal speed. Finally, we have extended the idea of Schamel to relativistic plasma, where the trapped and free particles are given by solutions of the relativistic Vlasov equation.…”
Section: Introductionmentioning
confidence: 99%